Occupational exposure to polychlorinated dibenzo-p-dioxins and dibenzofurans in a magnesium production plant. Issue 12 (December 1995) - Hansson, M; Grimstad, T; Rappe, C
Abstract : OBJECTIVES--The production of magnesium is a well known source of both aliphatic and aromatic chlorinated compounds, among others the polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs). The aim of this study was to establish whether increased concentrations of PCDDs and PCDFs could be found in the blood of workers in a magnesium plant. METHODS--Blood plasma from 10 workers, employed at a magnesium plant for 10 to 36 years, and from a control group consisting of nine people who had no direct contact with the production were studied. Isomer specific analyses of PCDDs and PCDFs by means of high resolution gas chromatography/high resolution mass spectrometry (HRGC/HRMS) techniques were performed. RESULTS--A significant increase was found in the concentrations of some of the congeners, mainly PCDFs, in the workers compared with the control group. Octachlorodibenzofuran (OCDF) is the congener that most strongly correlates with occupational exposure in the magnesium plant. Low concentrations of 1, 2, 3, 4, 6, 8, 9-heptachlorodibenzofuran were found in seven of the workers. Such isomers--that is, not 2, 3, 7, 8-substituted--are rarely found in human samples. CONCLUSION--Due to the long biological half lives and lipid solubility of PCDDs and PCDFs, blood analyses may serve as an index of past cumulative occupational exposure and a means of assessing a person's exposure situation.